Untensed fibronectin fibers: a novel hallmark of microthrombi - Arnaud Miéville; Petra Wolint; Nikola Cesarovic; Nikola Cesarovic; Volkmar Falk; Volkmar Falk; Viola Vogel (Frontiers in Cardiovascular Medicine)
BackgroundMyocardial Infarction with Non-Obstructive Coronary Arteries (MINOCA) accounts for up to 15% of acute Myocardial Infarction (MI) cases and presents significant diagnostic and therapeutic challenges. The specific targeting of microthrombi involved in microthrombi-induced MINOCA with molecule-specific precision has been challenging due to their omnipresence in the bloodstream, highlighting the need for novel biomarkers and imaging strategies. Fibronectin, one of these omnipresent extracellular matrix (ECM) proteins, exists in distinct physical states in healthy versus diseased tissues, presenting stretched versus untensed fibers, which may serve as potential diagnostic and therapeutic targets.MethodsThe peptide FnBPA5, a highly specific probe that binds selectively to untensed fibronectin fibers, as its multivalent binding motif is destroyed upon fiber stretching, was employed here to assess fibronectin's fiber tension in microthrombi before and after the onset of MINOCA in a pig model of autologous microthrombi-induced MINOCA.ResultsLoss of fibronectin fiber tension was identified here as a novel key feature of microthrombi in a pig model of autologous microthrombi-induced MINOCA, whereas fibronectin fibers in the surrounding healthy myocardium remained highly stretched. FnBPA5 can thus effectively visualizes fibronectin's physical signature, thereby distinguishing microthrombi from the surrounding healthy tissue.ConclusionThese findings underscore FnBPA5's unique capacity to discriminate not merely the presence of an abundant ECM molecule within a thrombus, but its distinct physical conformation. FnBPA5 enables the selective detection of microthrombi in coronary arteries by targeting untensed fibronectin fibers, a novel mechanical biomarker of microthrombi. Targeting a protein's physical state with high specificity makes FnBPA5 a promising tool for advanced microthrombi detection and for mechano-therapeutic strategies involving the targeted delivery of therapeutic agents.